2015
DOI: 10.1111/cxo.12242
|View full text |Cite
|
Sign up to set email alerts
|

FLORA™: Phase I development of a functional vision assessment for prosthetic vision users

Abstract: Background Research groups and funding agencies need a functional assessment suitable for an ultra-low vision population in order to evaluate the impact of new vision restoration treatments. The purpose of this study was to develop a pilot assessment to capture the functional vision ability and well-being of subjects whose vision has been partially restored with the Argus II Retinal Prosthesis System. Methods The Functional Low-Vision Observer Rated Assessment (FLORA) pilot assessment involved a self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 23 publications
(34 reference statements)
0
42
0
Order By: Relevance
“…The FLORA and VisQoL were performed only through post-implant year 3 (as per the clinical trial protocol), and the FLORA has been described and reported elsewhere. 10,11 The Activity Inventory was not fully validated in this patient population (e.g., with very low vision patients) and as such the data are not included in this report.…”
Section: Methodsmentioning
confidence: 99%
“…The FLORA and VisQoL were performed only through post-implant year 3 (as per the clinical trial protocol), and the FLORA has been described and reported elsewhere. 10,11 The Activity Inventory was not fully validated in this patient population (e.g., with very low vision patients) and as such the data are not included in this report.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the Functional Low‐Vision Observer Rated Assessment (FLORA) instrument was developed specifically for use in patients implanted with retinal prostheses who suffer from profound loss of vision or blindness. The structure and development of FLORA has been previously published . The instrument combines a self‐report section (Part 1) with a list of functional visual tasks that are rated by a qualified evaluator (Part 2).…”
Section: Introductionmentioning
confidence: 99%
“…The Argus II clinical trials have also included a new functional low-vision observer-rated assessment, which combines visual tasks scoring (eg, mobility tasks and activities of daily living), self-reported user experience, and case-study assessment (a modified quality of life questionnaire)27 by a rehabilitation expert, which showed 80% of patients reported that the device had a positive impact on their daily life at the 1-year follow-up 3…”
Section: Retinal Prosthesesmentioning
confidence: 99%